A Comparative Study of Tuberculosis Diseases in Diyala Province in 2010 and 2015 - Raghad Ibrahim (Journal of Global Pharma Technology, 2018)
Tuberculosis (TB) is one of the concern worldwide public health threats. A retrospective study conducted during the period (2016/11/14) until (2017/4/7) to comparative the incidence of tuberculosis disease in Diyala province between 2010 and 2015 years, the study-included number of patients with the chest and respiratory infections visited the central treatments of tuberculosis infections in Diyala. The patients included males and females with ages from (20-90) years, they had been done X-ray chest and laboratory tests, including: examination of the septum with Ziehl–Neelsen testand (E.S.R).Examination had been identified a positive cases of tuberculosis among them, the number of patients infection with TB in (2010) were (147) cases from (1429) and (405) cases from (5772) patients in (2015). The study showed that tuberculosis infections were decline in 2015 to 7% compares with 2010 to10.3% .The results showed that (44.89%) of male and 55.1% in female with TB infections in 2010. Also 47.90% of males and 52.09% of females infected with TB in 2015 , the high rate of infection among age group (31-50) in 2010, and (51-70 years) in 2015 , while the age group (71-90years) are showed the lowest ratio were infected with TB infections for both 2010 and 2015. The results appeared urban area were high incidence of infection in both 2010 and 2015 in contrast with rural area , was 85(52.82% ) in urban and 62(42.17%) in rural area in 2010 , with 207 (51.1%) in urban area and 198 ( 48.9%) in rural areas in 2015.Keywords: TB, Seroprevelance, Diyala province, Iraq.